Pengaruh lingkungan kerja, system pengawasan, dan motivasi kerja terhadap kinerrja karyawan di Zunagawa Sparepart - Ananda Prasastiningrum; Septyarini, Epsilandri (Universitas Widya Mataram, 2024)
This research aims to analyze the influence of the work environment, supervision system, and work motivation on employee performance at Zunagawa Spareparts. This type of research is quantitative descriptive. The population in this study were 30 employees at Zunagawa Spareparts Yogyakarta. All members of the population were used as respondents using the saturated sampling method. The type of data used in this research is quantitative data. Analysis and testing on the data is carried out in several stages. The first stage is validity and reliability, next is the classic assumption test, multiple linear analysis, then tests are carried out on the hypotheses (t and F tests) that have been formulated, finally analysis of the coefficient of determination (R2). The results of this research show that in part the work environment has a positive and significant effect on employee performance. The supervision system has a positive and significant effect on employee performance and work motivation has a positive and significant effect on employee performance. Simultaneously shows that the work environment, supervision system and work motivation have a positive and significant effect on the performance of Zunagawa Spareparts employees.